Prevalence and risk factors of common mental disorders among medical students - Lima, Maria Cristina Pereira (2006)
OBJECTIVE: To estimate the prevalence and assess risk factors of common mental disorders among medical students. METHODS: A cross-sectional study was carried out comprising 551 university medical students in the state of São Paulo, Southeastern Brazil. A self-administered questionnaire to collect sociodemographic and course-related data as well as the Self-Reporting Questionnaire were used. Both Chi-square test and logistic regression were used in data analyses. RESULTS: A total of 82.6% of the students enrolled in the course participated in the study. Most of them were women (61%), 60% aged between 20 and 23 years, and 99% were from other cities. The prevalence of common mental disorders was 44.7% and they were independently associated with: difficulty in making friends (OR=2.0), poor self-evaluation of academic performance (OR=1.7), thoughts of dropping out of the medical course (OR=5.0) and perceived lack of emotional support (OR=4.6). Although prevalence of these disorders was associated with the course period in the first analysis, this association was not maintained in the multivariate analysis. CONCLUSIONS: The prevalence of common mental disorders was shown to be high among medical students, associated with variables concerning support networks. Emotionally tense experiences such as dealing with seriously ill patients and peer group formation in the last years of the medical course are potentially strong stressors, especially for those with poor social support. It is suggested that educational institutions should be aware of that and make interventions aiming at treating and caring for the students' distress.